Statins and Myotoxic Effects Associated With Anti-3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Autoantibodies. Issue 4 (January 2015) - Watanabe, Yurika; Suzuki, Shigeaki; Nishimura, Hiroaki; Murata, Ken-ya; Kurashige, Takashi; Ikawa, Masamichi; Asahi, Masaru; Konishi, Hirofumi; Mitsuma, Satsuki; Kawabata, Satoshi; Suzuki, Norihiro; Nishino, Ichizo; et al.
<x xml:space="preserve">Abstract</x> Abstract Statins have a variety of myotoxic effects and can trigger the development of inflammatory myopathies or myasthenia gravis (MG) mediated by immunomodulatory properties. Autoantibodies to 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) have been identified in patients with statin-associated myopathy. The purpose of the present study is to develop an enzyme-linked immunosorbent assay (ELISA) of anti-HMGCR antibodies and to elucidate the clinical significance of anti-HMGCR antibodies in Japanese patients with inflammatory myopathies or MG. We enrolled 75 patients with inflammatory myopathies, who were all negative for anti-signal recognition particle and anti-aminoacyl transfer RNA synthetase antibodies. They were referred to Keio University and National Center of Neurology and Psychiatry between October 2010 and September 2012. We also studied 251 patients with MG who were followed at the MG Clinic at Keio University Hospital. Anti-HMGCR antibodies were detected by ELISA. We investigated demographic, clinical, radiological, and histological findings associated with anti-HMGCR antibodies. We established the anti-HMGCR ELISA with the recombinant protein. Protein immunoprecipitation detected autoantigens corresponding to HMGCR. Immunohistochemistry using muscle biopsy specimens revealed regenerating muscle fibers clearly stained by polyclonal anti-HMGCR antibodies and patients' serum. Anti-HMGCR autoantibodies were specifically detected in 8 patients with necrotizing myopathy. The seropositivity rate in the necrotizing myopathy patients was significantly higher than those in the patients with other histological diagnoses of inflammatory myopathies (31% vs 2%, P = 0.001). Statins were administered in only 3 of the 8 anti-HMGCR-positive patients. Myopathy associated with anti-HMGCR antibodies showed mild limb weakness and favorable response to immunotherapy. All 8 patients exhibited increased signal intensities on short T1 inversion recovery of muscle MRI. Of the 251 patients with MG, 23 were administered statins at the onset of MG. One late-onset MG patient experienced MG worsening after 4-wk treatment with atorvastatin. However, anti-HMGCR antibodies were not detected in the 251 MG patients except for one early-onset MG patient with no history of statin therapy. Anti-HMGCR antibodies are a relevant clinical marker of necrotizing myopathy with or without statin exposure, but they are not associated with the onset or deterioration of MG.